The effect of proportional v. value pricing on fountain drink purchases: results from a field experiment. Issue 13 (15th May 2018) - Gollust, Sarah E; Tang, Xuyang; Runge, Carlisle Ford; French, Simone A; Rothman, Alexander J
Abstract: Objective: Reducing sugar-sweetened beverage consumption is a public health priority, yet finding an effective and acceptable policy intervention is challenging. One strategy is to use proportional pricing (a consistent price per fluid ounce) instead of the typical value-priced approach where large beverages offer better value. The purpose of the present study was to evaluate whether proportional pricing affects the purchasing of fountain beverages at a university cinema concession stand. Design: Four price strategies for beverages were evaluated over ten weekends of film screenings. We manipulated two factors: the price structure (value pricing v . proportional pricing) and the provision of information about the price per fluid ounce (labels v . no labels). The key outcomes were the number and size of beverages purchased. We analysed data using regression analyses, with standard errors clustered by film and controlling for the day and time of purchase. Setting: A university cinema concession stand in Minnesota, USA, in spring 2015. Subjects: University students. Results: Over the study period (360 beverages purchased) there were no significant effects of the proportional pricing treatment. Pairing a label with the standard value pricing increased the likelihood of purchasing large drinks but the label did not affect purchasing when paired with proportional pricing. Conclusions: Proportional prices did not significantly affect the size of beverages purchased by students at a university cinema, but adding a price-per-ounce label increased large drink purchases when drinks were value-priced. More work is needed to address whether pricing and labelling strategies might promote healthier beverage purchases.